Management of root-knot nematodes (Meloidogyne spp.) in vegetable production systems in Africa: A comprehensive review and perspectives (Sciences et Technologies pour l’Agriculture Durable, 2025)
Vegetable production is vital for food security in Africa due to its nutritional richness, health benefits, and role in employment generation. Nevertheless, intensive production conditions, such as monoculture and the impacts of climate change, have strongly facilitated the establishment of numerous pathogens and diseases that limit crop yields. Among the various biotic pathogens, root-knot nematodes (RKNs, Meloidogyne spp.) are considered one of the most severe biotic pathogens in Africa because of their yield losses. The subterranean lifestyle of RKNs allows their proliferation across multiple crops over several years and facilitates their spread through farming practices, making their management challenging. Therefore, a systematic investigation of affected crops, nematode-induced yield losses, and available sustainable management options is necessary. A thorough literature search was conducted using databases such as Google Scholar, Scopus, and CABI, following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, to comprehensively analyze available data on RKNs and provide synthesized information on their occurrence in Africa, biology and life cycle, host plants, factors promoting their spread, yield losses, and control strategies. These insights are intended to support farmers, researchers, and policymakers in increasing vegetable production in a sustainable way in Africa, thereby contributing to food security. This review highlights the control potential and limitations of the main RKN management methods in Africa and proposes future research directions, particularly, integrated pest management approaches that emphasize biological and cultural control methods.